2021
DOI: 10.1001/jamaoto.2021.1976
|View full text |Cite
|
Sign up to set email alerts
|

Association of Multifocality With Prognosis of Papillary Thyroid Carcinoma

Abstract: hyroid cancer is the ninth most frequent cancer worldwide, and its incidence has risen dramatically. 1,2 There were 567 233 patients with newly diagnosed thyroid cancer in 2018, representing 3.1% of all cancer cases worldwide. Papillary thyroid carcinoma (PTC) comprises more than 80% of all thyroid cancers, and is usually associated with an excellent prognosis; 3 however, up to 30% of patients experience significant disease progression, including regional recurrences and distant metastases. [4][5][6] Researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 60 publications
2
27
0
1
Order By: Relevance
“…It is typically inert and usually shows excellent prognosis to standardized comprehensive treatments (including surgical resection, iodine ablation, and TSH inhibition therapies) (2). However, such clinical features of PTC as the large size of tumor, extrathyroidal extension (ETE), multifocality, lymph node metastasis (LNM), and distant metastasis (3)(4)(5)(6) still lead to a poor prognosis. As a distinctive risk factor for distant metastasis and postoperative local recurrence (7,8), LNM is prone to early PTC (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…It is typically inert and usually shows excellent prognosis to standardized comprehensive treatments (including surgical resection, iodine ablation, and TSH inhibition therapies) (2). However, such clinical features of PTC as the large size of tumor, extrathyroidal extension (ETE), multifocality, lymph node metastasis (LNM), and distant metastasis (3)(4)(5)(6) still lead to a poor prognosis. As a distinctive risk factor for distant metastasis and postoperative local recurrence (7,8), LNM is prone to early PTC (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Joseph, 60 Kim 61 and Zhang 62 et al performed meta‐analyses in 2018 and 2021, which reported that multifocality is positively correlated with lymph node metastasis (both in central and lateral compartments), advanced TNM stage and recurrence. Here, we conducted a more comprehensive analysis concerning unfavorable clinicopathologic features and time‐to‐event outcomes result from multifocal PTC, of which should be classified as a higher risk category.…”
Section: Discussionmentioning
confidence: 99%
“…The debate on whether familiarity can be counted as a risk factor in DTC patients is still ongoing, with some studies reporting more aggressive behavior and a higher rate of recurrence [28][29][30], and other studies finding no differences [31]. Still, the impact of microscopic ETE on disease recurrence is not clear, as some studies reported no difference between patients with and without microscopic ETE [32], while a recent meta-analysis documented an increased risk (with no effect on survival) [33].…”
Section: Discussionmentioning
confidence: 99%